The minor inequalities in the description of the set covering polyhedron of circulant matrices - Bianchi, Silvia María (2014)
In this work we give a complete description of the set covering polyhedron of circulant matrices Cskk with = 2, 3 and k ≥ 3 by linear inequalities. In particular, we prove that every non boolean facet defining inequality is associated with a circulant minor of the matrix. We also give a polynomial time separation algorithm for inequalities involved in the description.